Exploring Service Quality in E-Commerce Platforms: A Qualitative Analysis of Customer Experience in Shopee - Muhammad Dzaki Nur Hisyam; Dimasqhi Azzura Alvianto; Pashya Ammar Pondaaga (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study explores service quality dimensions and customer experience on the Shopee e-commerce platform through a qualitative literature review approach. Drawing on seven empirical studies published between 2022 and 2025, this research synthesizes findings on how service quality measured through the SERVQUAL and e-SERVQUAL frameworks shapes customer satisfaction and loyalty in the Shopee ecosystem. Key findings indicate that service quality has a positive and significant effect on customer satisfaction across multiple research contexts, with explained variance ranging from 65.4% to 76.9% (Erna AR, 2022; Aulia Dwi Sartika Murniyati, 2025). The Customer Satisfaction Index analysis by Nur Rahmah Hidayah et al. (2024) recorded an overall satisfaction score of 81.57% for Shopee, with responsiveness identified as the most critical dimension requiring improvement. Customer experience and e-service quality are further confirmed as significant drivers of repurchase intention and loyalty (Surya Chandra et al., 2022; Melandri, 2024). Despite overall positive satisfaction levels, persistent gaps exist in delivery speed, complaint handling responsiveness, and data privacy assurance. This study concludes that Shopee must continuously enhance its service quality across all five SERVQUAL dimensions, with particular focus on responsiveness and empathy, to sustain customer satisfaction and long-term loyalty in Indonesia's increasingly competitive e-commerce market.